Reimagining Blackness through posthumanist sculpture: an analysis of the works of Ghanaian artist, Sulemana Armiyaw - Armiyaw Sulemana; Jiang Tieli; Ebenezer Fiifi Mensah; Kwame Opoku-Bonsu (Cogent Arts & Humanities)
This paper offers a critical analysis of two portrait sculptures by Ghanaian artist, Sulemana Armiyaw that explores posthumanist possibilities in the conception of identity through sculpture. Through a multidisciplinary approach that blends posthumanist theory, art history, and racial studies, the article investigates how Sulemana’s sculptures offer new ways of looking at race, body, and identity beyond the historically framed black identities and Blackness. It deconstructs the artist’s claim, to test with posthumanist theories and practices, as well as possibilities that lie within the field. Authors believe that, by merging human and non-human elements, Sulemana complicates existing narratives and hierarchies, and opens up complex means of comprehending and conceiving black representations beyond established binaries. Authors shed light on the impact posthumanist propositions in artistic representation can have in the conception of complex modes of identities that are nuanced, expansive, and inclusive. The study suggests that, Blackness, like present identity constructs, as historically anthropocentric feature can be in future negotiations beyond biologism, cultural and political connotations.